Culture in English Language Teaching: A curricular evaluation of English textbooks for foreign language learners - Banaruee, Hassan; Farsani, Danyal; Khatin-Zadeh, Omid (Frontiers in Education, 2023)
A critical assessment of the current systematical planning and an in-depth review of the teaching materials efficiently improve fine educational materials to the benefit of developed learning and teaching contexts. In some countries, such as Iran, that belong to the expanding circle, according to Kachru (1986), local book writers provide EFL materials that may ignore sociopragmatic language components, particularly culture. There is a blind spot and massive gap in the related literature regarding the inclusion and organization of cultural knowledge in these textbooks. This study investigated culture in Iranian schools by conducting a nationwide survey to fill the gap. The investigation is based on the components of the curriculum administered and used in Iran: Vision 1, Vision 2, and Vision 3 (2018). The evaluation is aimed at two prospects; firstly, to interpret whether the English textbooks taught at high schools in Iran have standardized principles and elements regarding Communication and Cultures. Secondly, to investigate the extent to which cultural knowledge and technology as the curricular components are implemented in the Vision series. In this respect, the checklist developed by the American Council on the Teaching of Foreign Languages (ACTFL) was employed. The evaluation done by 120 EFL teachers reveals that Vision 3 is preferable and more desirable than Vision 1 and 2, yet not significantly. The evaluation based on the seven curricular components indicates that Vision textbooks have standards at a low level and are not designed and developed to enhance EFL learners' cultural competence in the target language. This study highlights the role of enhancing EFL learners' cultural awareness in the expanding circle of World Englishes.